Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (2025)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)
fs-ref-orig: Duong, P., Batista, R., Lizotte, M., Sauvé-Schenk, K. et Bouchard, L. (2024). Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario [infographic]. Data User Conference on Health. Ottawa. fs-code-orig: Duong-2024

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (2025)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p < 0.001) and Francophones (6.15%, p < 0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p < 0.001 and RR = 1.41, p < 0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)
fs-ref-orig: Réseau des services de santé en français de l’Est de l’Ontario. (2020). Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire. fs-code-orig: Réseau des services de santé en français de l’Est de l’Ontario-2020

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Centre de recherche en santé dans les milieux ruraux et du nord. fs-code-orig: Sanou-2020b

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique. Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal. fs-code-orig: Sanou-2020c

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)
fs-ref-orig: Thifault, M.-C. (2024). Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. Dans F. Charbonneau et M. Bock (dir.), Le moment Monfort dans la francophonie canadienne (p. 205-226). Presses de l’Université d’Ottawa. fs-code-orig: Thiffault - 2024

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)
fs-ref-orig: Thifault, M.-C. et LeBel, M. (2021). Dérives : une histoire sensible des parcours psychiatriques en Ontario français. Les Presses de l'Université d'Ottawa. fs-code-orig: Thifault-2021

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services